The prevalence of probable overactive bladder and associated risk factors among medical students in Jordan: a cross-sectional study - Saleh Abuorouq (18001597) (2024)
Background To discuss the impact of overactive bladder (OAB) on medical students. overactive bladder. is a chronic condition that causes sudden and intense urges to urinate, which can have significant physical and psychological effects on patients’ lives. The prevalence of OAB among medical students is relatively high, with some studies reporting rates as high as 35.4%. This research aims to shed light on the prevalence rates and risk factors associated with OAB among medical students in Jordan. Methods A cross-sectional study was conducted using an online self-reported questionnaire as the study tool. The questionnaire collected the sociodemographic, health, and academic characteristics of medical students, as well as the new 7-item OABSS score. Results Out of the total sample of medical students surveyed (n = 525), 44.5% reported experiencing symptoms of OAB. Furthermore, the analysis also revealed that there was a significant difference in the prevalence of OAB between the ages of medical students. In addition, the study also found that there was a significant association between OAB symptoms and basic years, positive history of diagnostic UTI, positive history of recent trauma, high stress, and taking certain medications. Conclusions The study highlights the need for further research in this area and emphasizes the possible implications of OAB for medical students, including the need for additional support and resources to manage the condition. Other Information Published in: BMC Urology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12894-023-01394-4